IT Service Management as a Determinant of Customer Experience in e-Business - Gil Villa, Alex Fidel (2025)
In the current digital ecosystem, where competition among e-Business platforms is becoming increasingly intense, customer experience has become a strategic differentiator. This study aimed to analyze how IT service management influences customer experience within e-Business platforms, identifying operational and technological factors that affect this relationship. A systematic review was conducted based on the PRISMA methodology, complemented by a scientometric analysis, covering publications from 2020 to 2025. The search was carried out in the Scopus, IEEE Xplore, ScienceDirect, SciELO, and Google Scholar databases, using combinations of key terms with Boolean operators. After applying inclusion, exclusion, and quality criteria, 20 relevant documents were selected. The results show that low personalization, limited meaningful interaction, fragmented implementation of IT frameworks, and weak data governance negatively affect user perception. Furthermore, a limited adoption of analytical tools was identified, which restricts the adaptive capacity of platforms. On the other hand, scientific production is mainly concentrated in Asia, with Indonesia, China, and Malaysia being the most prominent. It is concluded that improving customer experience in e-Business requires integrating smarter, more collaborative, and user-centered approaches to strengthen digital trust.